DEVELOPING READING AND WRITING ASSESSMENT FOR SEVEN GRADE STUDENTS OF SMP IN MERANGIN DISTRICT BASED ON SCHOOL-BASED CURRICULUM - Ira Maisarah (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Language has an important role in developing the intellectual, social, and emotion of the students. That’s why, the students must mastering some languages included English. In Indonesia, English has been taught since Junior High School. One of the purposes of learning English is the students are expected to have the basic competencies both oral and written forms to communicate effectively. To evaluate the improvement of students’ ability in English, the English teacher needs to assess the language competence of the students. Two of the students’ competences are reading and writing skill. The teacher can assess these skills by using authentic assessment. The authentic in authentic assessment usually means presenting students with tasks that are directly educationally meaningful instead of indirectly meaningful. It means, in creating assessment, the teacher must consider some aspects such us to whom they will assess, what part that they will assess, and for what the assessment given. For reading, the teacher can give text that closed by the students such as texts that are described about tourism places in Merangin District, etc. They can also add some comprehension questions to assess the students’ understanding related to the content of the text. Next, for writing, the teacher can ask the students to write about someone or doing something.  Both—reading and writing skills—can help the students to communicate in English.